The Evaluation of Temporary Shelter Areas Locations Using Geographic Information System and Analytic Hierarchy Process - Javad Junian; Valiollah Azizifar (Salehan Institute of Higher Education, 2018)
Earthquakes are notorious as devastating natural disasters that can result in tragic fatalities and economic loss. The building of earthquake evacuation shelters is an effective way to reduce earthquake consequences and protect lives. In present study, analytic hierarchy process (AHP) was applied as a multiple criteria of decision making (MCDM) method to investigate different shelter sites that belong to a disaster-prone area of the north of Iran. The principles of vulnerable areas, access to roads, firefighting centers, populated areas, fault lines, and medical centers were considered to determine optimal temporary shelter areas locations. With the support of a geographic information system (GIS), the method comprised three steps, i.e. selecting candidate shelters, analyzing the spatial coverage of the shelters, and determining the shelter locations. Finally, a case study was used to demonstrate the application of the multi-criteria model and the corresponding solution method and their effectiveness in planning urban earthquake evacuation shelters. It was found that the “distance from fault line” criterion of 0.429 could be the most effective factor along the others.